2023
DOI: 10.1210/clinem/dgad238
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Plasma Sodium Levels Is Associated With an Increase in Osteoblast Function in Chronic SIAD

Abstract: Context Hyponatremia is associated with increased risk for osteoporosis. Preclinical studies in untreated hyponatremia suggest osteoclast upregulation whereas a clinical study showed improved osteoblast fuction after hyponatremia normalization in hospitalized patients with syndrome of inappropriate antidiuresis (SIAD). Objective To investigate the impact of sodium increase on bone turnover, i.e. the ratio of the osteoblast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Moreover, the tonicity response to Fgf23 was not completely abolished in NFAT5 KO Osmoregulation and [Na + ] sensing mechanisms were mainly studied for cells in the hypothalamus (reviewed in 47 ). In line with studies from others 29,30,32 , we found that osteoblasts can sense osmotically relevant changes in [Na + ] and respond with an altered expression of several genes including Fgf23. Studies in RAW264.7 pre-osteoclastic cells showed increased osteoclast formation and resorptive activity in response to low [Na + ] concentration 20,21 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the tonicity response to Fgf23 was not completely abolished in NFAT5 KO Osmoregulation and [Na + ] sensing mechanisms were mainly studied for cells in the hypothalamus (reviewed in 47 ). In line with studies from others 29,30,32 , we found that osteoblasts can sense osmotically relevant changes in [Na + ] and respond with an altered expression of several genes including Fgf23. Studies in RAW264.7 pre-osteoclastic cells showed increased osteoclast formation and resorptive activity in response to low [Na + ] concentration 20,21 .…”
Section: Discussionsupporting
confidence: 91%
“…On a mechanistic level, both high AVP 26,27 and low [Na+] levels 19,28 are postulated to promote osteoclastogenesis and inhibit osteoblastogenesis, leading to bone loss in hyponatremia. Correction of hyponatremia in hospitalized patients has a positive impact on osteoblast function 29,30 . On the other hand, high [Na + ] may also enhance bone loss through an increase in osteoclastic resorption 31 .…”
Section: Significance Statementmentioning
confidence: 99%
“…However, in another study researchers found that when the doses of halofuginone were less than 10 μg/ml, no effect of halofuginone was evident on osteoclast abundance or morphology, reflecting that halofuginone had no direct effect on osteoclast formation, but was mediated by other factors [ 21 ]. P1NP is a byproduct of type I collagen synthesis and an indicator of bone formation and osteoblast function [ 22 , 23 ], and its serum concentration can reflect osteoblast activity and differentiation directly. We found that both the ALP + osteoblasts and the serum P1NP concentration increased obviously in the HF group, suggesting that halofuginone enhanced osteoblastogenesis by increasing osteoblast formation and activity.…”
Section: Discussionmentioning
confidence: 99%